Inconsecvența curții constituționale cu privire la regimul juridic al analogilor substanţelor stupefiante sau psihotrope [Articol] - Stati, Vitalie (CEP USM, 2018)
Considerentele reproduse în Decizia Curții Constituționale nr.43/2018 contravin argumentelor invocate în Adresa către Parlamentul Republicii Moldova inclusă în Hotărârea Curții Constituționale nr.25/2015. Aceasta deschide calea pentru comiterea de abuzuri în activitatea de aplicare a art.217 și 2171 CP RM. În pofida poziției exprimate în Decizia Curții Constituționale nr.43/2018, definiţia din alin.(6) art.1341 CP RM nu este clară, previzibilă şi lipsită de echivoc. Destinatarii legii penale nu pot avea o reprezentare clară asupra dispoziţiilor art.217 și 2171 CP RM (în partea ce se referă la analogi), astfel încât să-şi adapteze conduita şi să prevadă consecinţele ce decurg din nerespectarea acestor norme. Maniera ambiguă de redactare, precum și utilizarea unor sintagme neclare, sunt neconforme cu dispoziția de la alin.(2) art.23 din Constituție. Profitând de lipsa unor repere obiective, inclusiv normative, cei abilitați cu aplicarea legii penale au puterea discreționară să atribuie (în condiții obscure) unei substanțe statutul juridic de analog. Expertul este cel care conferă conținut conceptului de similaritate utilizat în alin.(6) art.1341 CP RM. În alți termeni, expertul este cel care stabilește limitele de aplicare a acestei norme penale. Calificarea oficială de către un expert a unei infracțiuni reprezintă nu altceva decât depășirea atribuțiilor de serviciu, intrând sub incidența art.328 CP RM sau a art.313 din Codul contravențional. În concluzie, stabilirea de către expert a cantității de analogi reprezintă un act de ilegalitate.

The paragraphs reproduced in the Constitutional Court's Decision No.43/2018, contradicts the Courts arguments put forward by it in the Address to the Parliament of the Republic of Moldova and included in the Constitutional Court Decision No.25/2015. This opens the way for potential abuses in the application of art. 217 and art.2171 PC RM. Notwithstanding the position expressed in the Constitutional Court Decision No.43/2018, the definition in par.(6) art.1341PC RM is still not clear it is predictable and unambiguous. In this context, the appliers of penal law cannot have a clear representation of art.217 and art.2171 PC RM (the paragraphs addressing the analogues issue) so as to adapt their conduct and to foresee possible consequences as a result of the non-compliance to these rules. The ambiguous editing, as well as the use of unclear syntax makes it diverge from the provision of par.(2) art.23 of the Constitution. Taking advantage of the lack of objective benchmarks, including normative ones, the penal law enforcement authorities have discretionary power to attribute (in unclear terms) a substance to the legal status of an analogue. It is the expert the one the one who is entitled to confer the quality of similarity used in par.(6) art.1341 PC RM. In other terms, it is the expert who sets the limits of the application of this penal rule. A official qualification made by an expert in relation to an offence is nothing more than a breach of the work duties and it falls under art.328 PC RM or art.313 of the Contravention Code.In conclusion, it is illegal for an expert to determine the amount of analogues.
THE INCONSISTENCES OF THE CONSTITUTIONAL COURT WITH REGARD TO THE LEGAL STATUS OF THE ANALOGUES OF NARCOTIC OR PSYCHOTROPIC SUBSTANCES
Keywords: substanțe stupefiante; substanțe psihotrope; Curtea Constituțională; previzibilitate; narcotic substances; psychotropic substances; Constitutional Court; predictability; expert